O direito à saúde no brasil: uma análise dos impactos do golpe militar no debate sobre universalização da saúde / The Right to Health in Brazil : An analysis of the impact of the military coup in the debate on universalization of Health - Carvalho, Rodrigo Badaró de; dos Santos, Thaís (Revista do Programa de Pós-Graduação em Direito, 2015)
This article seeks to understand how the military dictatorship established in 1964 influenced the discussion and the public health policies aimed towards the universalization of health in Brazil. The literature on the subject was analyzed in order to retrace the condition of the debate on the universalization of the access to health services in the period prior to 1964. The paper also lists the public health policies adopted by the military regimen, in an attempt to understand if there had been any continuity to the ideas of former governments. On one hand, there had been developments concerning the scope of public services, by the creation of public policies during the military government. However, many of these developments were aimed towards the private sector and based on curative medicine. On the other hand, on 1963, during the III National Health Conference, some elements which were essential to the creation of SUS after the 1988’s Constitution stood out.